2013
DOI: 10.3389/fpls.2013.00268
|View full text |Cite
|
Sign up to set email alerts
|

Sulfide as a soil phytotoxin—a review

Abstract: In wetland soils and underwater sediments of marine, brackish and freshwater systems, the strong phytotoxin sulfide may accumulate as a result of microbial reduction of sulfate during anaerobiosis, its level depending on prevailing edaphic conditions. In this review, we compare an extensive body of literature on phytotoxic effects of this reduced sulfur compound in different ecosystem types, and review the effects of sulfide at multiple ecosystem levels: the ecophysiological functioning of individual plants, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
208
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 279 publications
(237 citation statements)
references
References 152 publications
4
208
0
1
Order By: Relevance
“…Sulfide is known to be very toxic to seagrasses (Calleja et al, 2007;Koch and Erskine, 2001;Lamers et al, 2013;Marba et al, 2006;Terrados et al, 1999) and Van der Heide et al (2012) showed a negative effect on Zostera noltii biomass production at porewater sulfide levels <200 mol L -1 . We found similar threshold values in our field experiment and also found that patch expansion was entirely blocked by sulfide concentrations >1000 mol L -1 .…”
Section: Sulfide Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfide is known to be very toxic to seagrasses (Calleja et al, 2007;Koch and Erskine, 2001;Lamers et al, 2013;Marba et al, 2006;Terrados et al, 1999) and Van der Heide et al (2012) showed a negative effect on Zostera noltii biomass production at porewater sulfide levels <200 mol L -1 . We found similar threshold values in our field experiment and also found that patch expansion was entirely blocked by sulfide concentrations >1000 mol L -1 .…”
Section: Sulfide Toxicitymentioning
confidence: 99%
“…Sulfide is a strongly phytotoxic compound, as it blocks the activity of cytochrome oxidase and other metal containing enzymes (Lamers et al, 2013). It is formed in anaerobic sediments rich in organic matter, where sulfate is used as an alternative terminal electron acceptor during the microbial breakdown of organic matter (Gray and Elliott, 2009;Holmer and Nielsen, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Sulfide was measured according to the method described in Govers et al [36]. We measured porewater sulfide concentrations since this indicates sediment anoxia (sulfide is only produced in anoxic conditions), and sulfide is toxic to most eukaryotic life, including marine plants [40] and perhaps also oomycetes, potentially affecting seed survival and infection by Phytophthora and Halophytophthora species.…”
Section: (E) Chemical Sample Analysismentioning
confidence: 99%
“…Sea water incursion increases salinity but also alters sulfate concentrations by orders of magnitude as fullstrength seawater has 10-1000X more sulfate than freshwaters [Lamers et al, 2013]. Sulfate reduction to sulfide, via microbial respiration, follows nitrate and iron reduction as the next most thermodynamically favorable reaction to microbes [Stumm and Morgan, 1996].…”
Section: Introductionmentioning
confidence: 99%